Cardiovascular toxicity of targeted therapies for cancer: a protocol for an overview of systematic reviews. Issue 6 (27th June 2018) - van Leeuwen, Marina T; Luu, Steven; Gurney, Howard; Brown, Martin R; Webber, Kate; Pearson, Sallie-Anne; Hunt, Lee; Vajdic, Claire M
Abstract : Introduction: The introduction of targeted therapies for cancer has contributed to dramatic improvements in patient survival. Nevertheless, several targeted therapies have been associated with 'off-target' adverse effects, based on varying levels of evidence. To date, this evidence has not been systematically synthesised. We will synthesise published systematic review evidence of cardiovascular toxicity associated with targeted cancer therapies. Methods and analysis: We will include systematic reviews of randomised controlled trials and observational studies that report on cardiovascular outcomes for individual agents. We will identify systematic reviews by applying predeveloped, standardised search strategies within Embase, Medline and Cochrane Central. Two independent reviewers will identify reviews published up to 31 December 2016 using predefined eligibility criteria. They will resolve ambiguous cases through consensus, arbitrated by a third reviewer if required. The reviewers will extract and report data according to methodological guidelines for overviews provided by the Cochrane Collaboration, Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. They will assess the quality of included reviews by applying the Assessment of Multiple Systematic Reviews tool. They will judge the quality of evidence in included reviews based on their assessment of bias and incorporation into the interpretation of findings. In synthesising the evidence, we will classify agents based on systematic review evidence of toxicity (sufficient, probable, possible or indeterminate) for specific cardiovascular outcomes (congestive heart failure, myocardial infarction, ischaemic heart disease, left ventricular ejection fraction decline, cerebrovascular disease, pulmonary embolism, thrombosis and hypertension). This will provide clinicians and patients with an accessible synthesis based on robust methodology. Ethics and dissemination: Ethics approval is not required for overviews. We will conduct the study in collaboration with consumer representatives. We will submit results for peer-review publication, and disseminate them through established clinical and consumer networks. PROSPERO registration number: CRD42017080014.